Review of the genus Ceraturgus Wiedemann (Diptera: Asilidae) in North America north of Mexico - Barnes, Jeffrey K. (Zootaxa, 2008)
The species of Ceraturgus occurring in the eastern United States and Canada are reviewed. A key to species, descriptions, illustrations of wings and some genitalic features, and distribution maps are presented. Ceraturgus fasciatus is resurrected from synonymy with Ceraturgus cruciatus, and Ceraturgus mabelae is reduced to synonymy with Ceraturgus nigripes (new synonymy). Ceraturgopsis is resurrected, assigned subgeneric rank, and Ceraturgus cornutus is fixed as type species. This work is dedicated to the memory of one of America’s foremost asilidologists, Joseph Wilcox.